(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The subject of this article is the reception of Mark Arenstein’s stage activity in the Polish-language press published in the interwar period. The content analysis of announcements, reviews, interviews and press polemics aimed to verify how Polish journalists perceived Arenstein’s conception of Polish-Jewish theatre, implemented by the director, among others, by staging in the Polish language plays belonging to the canon of Yiddish literature. The study showed that the supporters of the director’s initiatives emphasized that they contributed to the deepening of contacts between Polish and Jewish artists and increased the knowledge of the Polish audience about Jewish tradition. Some journalists, however, questioned Arenstein’s idea of using theatre as an instrument of Polish-Jewish cultural dialogue. They pointed out that, despite the director’s efforts, Polish viewers were generally unable to correctly understand his plays because they were deprived of any knowledge of Jewish theatre. Fierce opposition to Arenstein’s theatrical activity was formulated by journalists associated with national democracy, who treated his theatre productions in Polish as a threat to national culture and unfair competition for Polish directors and playwrights.